Turning weeds into drugs: The prospect of Mimosa pudica for Diabetes mellitus in-vitro - Tunna, Tasnuva Sarwar; Sarker, Md. Zaidul Islam; Ahmed, Qamar Uddin; Md. Jaffri, Juliana (2014)
In our quest with respect to proposing alternative medicinal source against the global threat diabetes mellitus, a weed i.e. Mimosa pudica has been studied for its anti-diabetic potential. This study aimed to investigate in vitro inhibitory activity against diabetic enzymes (i.e. α-amylase & α-glucosidase) to evaluate potency of the weed against diabetes mellitus as well as to perform thorough chemical profiling using GCMS-Q-TOF, both done for first time for this weed, to assess the probable compounds present that could be linked to antidiabetic activity. Total phenolic and flavonoid contents along with DPPH radical scavenging assays were also done on five different extracts and fractions of M. pudica. Chemical class identification followed by derivetisation of the samples to analyse through GCMS was also done. Results showed good inhibitory activity against both the enzymes as compared to standard i.e. acarbose. At 1mg/mL, the MeOHi and EtOAc extracts showed two and three fold higher activity then the standard, respectively. Chemical profiling of all the extracts through GCMS- Q-TOF analysis identified organic acids, quinolone, quinone, phenolic compounds and dodecaborane as major constituents. Presence of highly radical scavenging dodecaborane is being reported for the 1st time in M. pudica. This study revealed that extracts of M. pudica is a rich source of phenolic compounds, dodecaborane, and organic acids and showed considerable high enzyme inhibitory activity. Extracts of M. pudica could be further subjected to isolation to identify the active principles responsible for its antidiabetic activity.